2022
DOI: 10.1177/0306624x221139037
|View full text |Cite
|
Sign up to set email alerts
|

Dark Traits, Harassment and Rape Myths Acceptances Among University Students

Abstract: The convergence of Machiavellianism, narcissism, psychopathy and sadism is known as the “Dark Tetrad.” Our understanding of the relationship between the Dark Tetrad, harassment and Rape Myths is limited. While men are more likely to blame victims of sexual violence, it is unclear how gender influences the ability to perceive harassment. The aim of the present study is to look at the relationship between dark traits, gender, Rape Myths and perception of harassment. A sample of N = 210 university students locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…Everyday sadism entails aggression that is pleasure-driven and involves the infliction of physical and emotional pain on others to humiliate, punish or control them (Longpré et al, 2020a). In contrast to the important empirical work on the facets of the Dark Triad, research on everyday sadism is more limited, and the concept is often studied from the perspective of criminal behavior and sexual sadism (Buckels et al, 2013;Longpré et al, 2022). However, Longpré et al (2020b) have shown that sadism extends beyond a sexual disorder found in criminal populations, and in its subclinical form, it can predict maladaptive behaviors and delinquency such as traditional and online bullying (Geel et al, 2017), white-collar crime (Amos et al, 2022), sexual violence (Beckett & Longpré, 2022;Russell et al, 2017), atypical sexual violence , stalking (Tachmetzidi Papoutsi & Longpré, 2022), and homicide (Monckton-Smith et al, 2017).…”
Section: The Dark Triad and Sadismmentioning
confidence: 99%
See 4 more Smart Citations
“…Everyday sadism entails aggression that is pleasure-driven and involves the infliction of physical and emotional pain on others to humiliate, punish or control them (Longpré et al, 2020a). In contrast to the important empirical work on the facets of the Dark Triad, research on everyday sadism is more limited, and the concept is often studied from the perspective of criminal behavior and sexual sadism (Buckels et al, 2013;Longpré et al, 2022). However, Longpré et al (2020b) have shown that sadism extends beyond a sexual disorder found in criminal populations, and in its subclinical form, it can predict maladaptive behaviors and delinquency such as traditional and online bullying (Geel et al, 2017), white-collar crime (Amos et al, 2022), sexual violence (Beckett & Longpré, 2022;Russell et al, 2017), atypical sexual violence , stalking (Tachmetzidi Papoutsi & Longpré, 2022), and homicide (Monckton-Smith et al, 2017).…”
Section: The Dark Triad and Sadismmentioning
confidence: 99%
“…Positive relationships have also been found between everyday sadism, sexual assault, Rape Myth acceptance, and coercion amongst men (Koscielska et al, 2019;Longpré et al, 2022;Russell & King, 2016). Evidence indicates that highly sadistic individuals might be able to commit these acts and avoid feelings of guilt due to the psychological rationalizations they employ (Longpré et al, 2022). Everyday sadism is thought to originate from defective moral reasoning (Buckels et al, 2019), which could be linked to a greater endorsement of Rape Myths.…”
Section: Rape Mythsmentioning
confidence: 99%
See 3 more Smart Citations